Shanghai Experimental Free Trade Zone - V. Ya. Portyakov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
In 2013 the People’s Republic of China has entered the second stage of foreign economic openness. If at the first stage, which started in the late 1970s as an integral part of the overall reform policy, China focused primarily on attracting foreign equipment and technologies, knowledge, and capital, at the new stage, the sending abroad Chinese capital, goods, services, and technologies becomes at least an equal task. One of the most important elements of this stage is the creation of experimental free trade zones (EFTZ), designed to help China master the most advanced world rules and regulations for conducting trade, investment activities, and international financial transactions. The first such zone was created in 2013 in Shanghai. At the very end of 2014, EFTZ were established in Tianjin, Fujian and Guangdong. This event was followed by the creation of zones in 7 more provinces of the PRC (5 of which are in the inner and Western regions of the country). In 2018, Hainan island was declared a free trade zone, and in the summer of 2019 EFTZ were established in six other regions of China. China’s experimental free trade zones have been in existence for more than six years. They have accumulated a variety of operational experience, which is also being implemented in national practice and is partially reflected in this article. The article focuses on the Shanghai EFTZ. The article shows changes in its format and describes features of zone’s development at the initial stage of 2013‑2015, in the dynamic period of 2016‑2017 and in the context of complex external economic conditions (2018‑2019). This text was prepared on the basis of original Chinese‑language sources, including official statistical materials of Shanghai. Useful information was also obtained during a visit to the Shanghai EFTZ in April 2019, organized with the assistance of the Consulate General of the Russian Federation in Shanghai.